(untitled) (Journal of Academic Research, 2021)
This study aimed to test the relationship between external audit and internal audit in the Libyan environment by identifying the level of cooperation between the external auditors and the auditors of the Libyan companies, Following the descriptive analytical approach, and to collect the study data, the questionnaire was distributed to the sample of the study, The study found that (regular meetings, timing of work, fraud notifications, training) as these variables affect the level of cooperation between the external and internal auditors. The variables auditors’ experience, exchange of reports, communications, audit plan have no impact on the level of cooperation between external auditors and auditors entering Libya companies